Modeling and computations in electromagnetics : a volume dedicated to Jean-Claude Nédélec - Ammari, Habib (Lecture Notes in Computational Science and Engineering, 2008)
This is nothing less than an essential text in what is a new and growing discipline. Electromagnetic modeling and computations is expanding as a result of the steadily increasing demand for designing electrical devices, modeling electromagnetic materials, and simulating electromagnetic fields in nanoscale structures. The aim of this volume is to bring together prominent worldwide experts to review state-of-the-art developments and future trends of modeling and computations in electromagnetics.